Decentralisation of Education in Karnataka - Sadananda, J.S.; Chandrashekhar, E.; Pushpa, B.S.; Kavita, P.N. (INDIAN EDUCATIONAL REVIEW, 2009)
With the phenomenal expansion of the formal educational system there has been a considerable progress in universalisation of elementary education. However, a large number of children have still remained outside the school. Further, a large segment of children from marginalised groups continue to be deprived of primary education. It is in this context that the present study was taken up to address the problems in the spread and strengthening of elementary education and the ability of Panchayats to resolve them without creating new ones.